Praktik Telekonseling Berbasis Teknologi Digital: Studi Kualitatif Layanan Kesehatan Mental di Indonesia - Alfiane Suci Setyasri; Galuh Andina Putri; Camelia Malik (Muthmainnah: Jurnal Bimbingan Konseling Islam dan Psikosufistik, 2025)
Digital transformation and the COVID-19 pandemic have accelerated the adoption of telecounseling as an alternative mental health service in Indonesia, despite persistent technical and ethical challenges. This study aims to describe technology usage in telecounseling and identify its advantages and challenges. Employing a qualitative descriptive approach, primary data were collected through semi-structured interviews with nine participants (platform providers, counselors, counselees) across six telecounseling platforms, supported by secondary data triangulation. Findings reveal telecounseling operates through three primary modalities—video conferencing (dominant), chat (flexible), and telephone (complementary)—offering advantages of wide accessibility, guaranteed privacy, and time/cost efficiency, alongside challenges including nonverbal communication limitations, internet connectivity issues, and crisis management complexities. This research contributes to mapping contextually relevant best practices for Indonesian telecounseling, recommending multimodal SOPs, digital competency training for counselors, and structured crisis referral protocols to optimize service delivery.